An FFT Based Fast Poisson Solver on Spherical Shells (Communications in Computational Physics, 2011)
We present a fast Poisson solver on spherical shells. With a special changeof variable, the radial part of the Laplacian transforms to a constant coefficient differentialoperator. As a result, the Fast Fourier Transform can be applied to solve thePoisson equation with O(N3logN) operations. Numerical examples have confirmedthe accuracy and robustness of the new scheme.